(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This paper examined some phonological processes in Bini based English, a sub-variety of Nigerian English, and compared these processes with Received Pronunciation (RP) to assess conformity levels. Purposive samples of twenty (20) Bini speakers of English were recorded, and their pronunciations were compared to the RP model using the International Phonetic Alphabet (IPA) for accuracy. Specifically, the study identified and analysed dominant phonological processes in the pronunciation of the subjects, using the framework of Generative Phonology. The processes include consonant deletions (e.g., the omission of final consonants), vowel substitution (e.g., the schwa being replaced by stronger vowels), consonant insertion, stopping, depalatalization, vocalization, and metathesis. Notably, these Bini-English bilinguals demonstrated a high level of deviation from RP norms, with specific challenges in consonant insertion and vowel reduction. Findings in the study revealed that Bini speakers of English have fairly internalized English phonological rules as only 47.98% (approximately 48%) could appropriately pronounce the words while a remarkable proportion of approximately 52% were unable to pronounce the words correctly. This is apparently because of the influence of mother tongue on the speech production of the subjects, and also because English phonological and orthographical systems are different from those of their indigenous language. It is based on these findings that the study affirms that nativisation, which is a product of language contact, is inevitable in the Nigerian situation.